Intergenerational income persistency in urban China - Deng Quheng; Björn Anders Gustafsson; Shi Li (Institute for the Study of Labor (IZA), 2012)
Intergenerational income elasticities are estimated using samples for urban China (covering many cities) for the years 1995 and 2002 and compared with results from other studies. We find that the income relation between the pairs: sons and fathers, sons and mothers and daughters and mothers, are in 2002 all similar in magnitude. In contrast the relation between daughters' and fathers' income is weaker. The income relationship between offspring and mothers was weaker in 1995 than in 2002. Our preferred estimates of income persistency for the son-father pairs of 0.47 for 1995 and 0.53 for 2002 are higher than what has been reported in the literature for several high-income countries with large welfare states. The strength of the income link between sons and fathers in urban China appears to be not very different from what has been reported for countries such as Brazil, Chile and the United States.
Keywords: D31; J62; P32; 330; intergenerational income mobility; China; Generationenbeziehungen; Einkommenselastizität; Soziale Mobilität; Stadtbevölkerung; China